Winer’s solitary congenital nodular calcification of the skin. - Khorchani, H.; Moussa, A.; Belhadj Ali, H.; Amri, M.; Zakhama, A.; Zili, J. (European Journal of Pediatric Dermatology, 2004)
Solitary congenital nodular calcification of the skin (of Winer) is included in the category of idiopathic calcinosis cutis occurring without evidence of local tissue injury or systemic metabolic disorder. We report herein a case of small solitary nodular warty lesion developed on the heel of a 4-year-old boy since birth. Histological examination showed several calcium deposits within the dermis with a transepidermal elimination pattern. Clinical and histological features of our case were similar to previously reported cases of Winer’s solitary congenital nodular calcification of the skin. The pathogenesis of this rare disorder remains unknown. Trauma is proposed to be a possible pathogenic factor particularly in cases developed on the ear.